Assistance in Utilizing Fruit Market Organic Waste for Maggot Cultivation for Fish and Poultry Breeding Communities in Mojokerto Regency - Sa'dibih, Muhammad Ahmad Fulka; Kumalasari, Dewi (Jurnal Soeropati, 2024)
The aim of this mentoring activity is to increase the understanding, skills and capacity of fish and poultry farmers in Mojokerto Regency in developing a maggot cultivation system by utilizing organic waste from the fruit market. This mentoring activity uses a participatory approach with the participatory rural appraisal method, namely by placing the community as the subject and the service team as insiders who are active in implementing the activities carried out. Based on the evaluation of the results of implementing community service assistance activities related to Assistance in the Use of Fruit Market Organic Waste for Maggot Cultivation for the Fish and Poultry Farmer Community in Mojokerto Regency, this assistance activity was successful in providing participants with an in-depth understanding of the use of organic waste for maggot cultivation. The practical implementation of the training material shows that participants are able to apply the concepts they have learned in their respective environments.